Planning and Budgeting of Tourism Sector in West Nusa Tenggara - Bayu Kharisma; Adhitya Wardhana; Ade Marsinta Arsani; Haposan Indra Wesly Pasaribu (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
West Nusa Tenggara is one of the central province of tourist destinations in Indonesia. This study aims to identify the consistency between planning and budgeting of the tourism sector in West Nusa Tenggara Province. Consistency analysis is done by analyzing the vision, mission, program, and budget. In addition, it compares planning and budgeting according to variance and percentage change between documents. The results showed that the level of consistency of the RPJPD and RPJMD as well as the RKPD in West Nusa Tenggara Province could be categorized as